The Influence of AI-Based Marketing Strategies on Customer Experience and Loyalty in the Age of Personalization - Muhammad Khoirul Umam (Journal of Strategic Marketing and Applied Economics, 2025)
Digital transformation in the era of personalization has significantly changed the marketing landscape, especially with the adoption of artificial intelligence (AI) allowing for a more personalized approach to creating unique customer experiences. The research aims to explore how AI-based marketing strategies affect customer experience and their loyalty to brands. Using a qualitative approach, the data was collected through in-depth interviews with industry experts and customers who interacted with brands that use AI technology in marketing. Thematic analysis is used to understand how AI-based personalization affects customer perception, satisfaction, and emotional attachment. The results show that responsive and relevant AI strategies significantly improve the customer experience, especially in terms of personalization and interactive engagement. In addition, these positive experiences are an important foundation in building long-term loyalty. This research offers valuable insights for companies on the importance of strategically applying AI in marketing to strengthen emotional relationships with customers.